As políticas da insegurança : da Scuderie Detetive Le Cocq às masmorras do novo Espírito Santo - Bittencourt, Matheus Boni (2014)
This dissertation aims at analyzing policies for public safety and criminal justice in the Espírito Santo between 1989 and 2013, using a historiographic methodology noting the distance between the official goals and practical consequences. In the first chapter, I focus on the historical context of the criminal policies, analyzing organizational formation of the Brazilian punitive system. I put emphasis, on the one hand, on the militarization process, i.e., the adoption of military models of hierarchy, discipline and training in public safety agencies, and on the other, and in any subsequent criminal laws approved by Congress. Such national processes are reflected in the Espírito Santo, where they spread "death squads" as Scuderie Le Cocq, but there was no public safety policy. The first comes amid serious political crisis between 1999 and 2002. But their purposes are more advanced with the administrative reform after 2003, when the government tries to impose models of business management and public-private partnerships on the state administration, including public safety and prison system. With this, there is a rapid expansion of selective incarceration in extreme overcrowding and violence, developing a prison industry. In the second chapter, I perform an analysis in which relate criminal, prisons, economic and demographic data, both in the context of Brazil and of the Espírito Santo. I note that state repression has "preference" for men, blacks, youngs and people with low educational level; for drug crimes and against property, with the increasing use of pre-trial detention. The Espírito Santo selective incarceration grows at a faster rate than the national average, which is reflected in the profile of the prison population, which is even more black, young and poorly educated and arrested for trafficking and drugs and pre-trial detained, with frequent justified denounces of torture, killings and enforced disappearances among the criminalized populations.